2020
DOI: 10.1063/5.0014485
|View full text |Cite
|
Sign up to set email alerts
|

Particle modeling of vacuum arc discharges

Abstract: Metal vapor vacuum arcs (VAs) are widely used in various fields of industry, such as circuit breakers, ion sources, electrical thrusters, and deposition systems. VAs usually originate from metal vapors eroding from the surface of a cathode, where they burn as tiny bright points, hence their name “cathode spots” (CS). Due to their high plasma density, short life span, and micrometer scale, the in situ and non-intrusive diagnostics of CS are a challenge. Numerical simulation is one method used to study CS with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…Since arcing itself is a high-density and high-temperature plasma that causes severe damage to material surfaces [7][8][9][10][11][12] , it has received enormous attention in research fields as well as industry for over 120 years 13 . Numerous studies have revealed arcing initiation mechanisms in direct current (DC) and radio frequency (RF) voltage environments in ultra-high vacuum, like field emission 14 and thermo-field electron emission 15 induced by a high electric field, which is on the order of several tens of GV/m and realized under circumstances of several tens of kV with micro-gaps 16 . Besides ultra-high vacuum conditions, arcing has also been observed in middle vacuum with low-temperature plasmas (LTPs), and several studies have investigated its ignition mechanisms [17][18][19][20] .…”
mentioning
confidence: 99%
“…Since arcing itself is a high-density and high-temperature plasma that causes severe damage to material surfaces [7][8][9][10][11][12] , it has received enormous attention in research fields as well as industry for over 120 years 13 . Numerous studies have revealed arcing initiation mechanisms in direct current (DC) and radio frequency (RF) voltage environments in ultra-high vacuum, like field emission 14 and thermo-field electron emission 15 induced by a high electric field, which is on the order of several tens of GV/m and realized under circumstances of several tens of kV with micro-gaps 16 . Besides ultra-high vacuum conditions, arcing has also been observed in middle vacuum with low-temperature plasmas (LTPs), and several studies have investigated its ignition mechanisms [17][18][19][20] .…”
mentioning
confidence: 99%
“…The MC swarm calculation is also performed by an inhouse PIC-DSMC code with the implemented anisotropic ionization model, which is initially designed for simulation on vacuum arcs [122][123][124]. The electron number is not fixed during ionization [25]: the initial electron number is 10 4 , and the simulation stops if the electron number reaches 10 7 .…”
Section: A Short Example Of Anisotropic Ionization Collisions In Hydr...mentioning
confidence: 99%
“…This approximation is not suitable for describing the transport of particles under vacuum conditions. Kinetic or hybrid approaches are also used [15][16][17]. Most of them are implemented by PIC/MCC methods (Particle-in-cell/Monte-Carlo).…”
Section: Introductionmentioning
confidence: 99%